Kick-off meeting on "Piloting and scaling of low emission development options in large-scale dairy farms in China" - Zijlstra, Jelle; Dong, Hongmin; Wei, Sha (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The cooperative project of the Consultative Organization for International Agricultural Research (CGIAR) on “Piloting and scaling of low emission development options in large-scale dairy farms in China” which jointly applied by the Institute of Environment and Sustainable Development in Agricultural, Chinese Academy of Agricultural Sciences (CAAS-IEDA), China Agricultural University and Wageningen University & Research has obtained approval. The project is an important part of the "Climate Change, Agriculture and Food Security" project. The objectives of this project are: -dentify potential mitigation options dairy in CN -Evaluate the feasibility of mitigation options for implementation in dairy production systems in China. -Engage stakeholders and next users to enhance implementation and scaling of mitigation options Contents of the meeting - Introduction of the project -Implementation plan and progress of the project -Discussion and improvement of implementation plan